Fatwa on Suicide Bombing in Sharia Maqāṣid View - Hannani; Damaisar, Reza (MUI Sulawesi Selatan, 2022)
The legal methodology of halalizing suicide bombings through fatwas has become a very worrying problem to date, making some people affected by the fatwa suicide bombing. This article aims to identify the basis for suicide bombing fatwas. This study discusses the methodology used by clerics to legalize suicide bombings. The controversial phenomenon of suicide bombings within the framework of Islamic law requires an approach based on the main principles of Sharia Maqāṣid. The main purpose of Islamic law is to protect the five fundamental maqāṣid (purposes): religion, soul, reason, heredity, and property. In this context, fatwas on suicide bombings have given rise to various views among Muslim religious scholars and thinkers. This type of research uses a type of qualitative research with library research methods that take from journal books and other books or we know as descriptive qualitative research types. Through a descriptive-analytical approach, this study outlines the arguments used by opinions that consider suicide bombing as a form of legitimate struggle and opinions that reject it as a violation of humanitarian and religious principles. The results showed that opinions that saw suicide bombings as an act that violated the principles of Sharia Maqāṣid were more strongly supported. These actions threaten key values such as the protection of life and reason, and disrupt the harmony of society. Although the arguments of supporters of suicide bombings often refer to extreme situations and occupation, Sharia Maqāṣid analysis shows that such goals do not justify the sacrifice of innocent lives. Fatwas on suicide bombings must be assessed through the lens of Sharia Maqāṣid in order to understand their impact on the main objectives of Islamic law. Views that promote human, peaceful, and just values are more consistent with the principles of Sharia Maqāṣid, while views that justify acts of indiscriminate violence should be examined more deeply in the context of their legitimacy and implications for society and religion as a whole.